Pengembangan SIBAKOS dengan Teknologi Live Preview Berbasis MyWebAR pada UMKM Barbershop di Lowokwaru Kota Malang - Ramdhani, Muhammad Ilham; Salsabila, Nabila; Widiyaningtyas, Triyanna; Sari, Heni Vidia (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to develop a website-based information system called SIBAKOS (Koko Salon Barbershop Information System) to address the operational problems of a barbershop MSME through online reservation and live preview features. The implementation methods included participatory system design, development of live preview and online reservation features, system implementation, functional testing using the black-box method, and direct training. Evaluation instruments consisted of field observations, interviews, and daily reservation data records, which were analyzed descriptively using quantitative methods. The results showed that SIBAKOS successfully facilitated the management of daily reservations through a structured system, reduced overlapping schedule cases from 5–7 cases per week to 1–2 cases per week, and improved operational efficiency by 78%. The live preview feature using MyWebAR provided visual references that facilitated communication between customers and salon staff, reducing consultation time by an average of 3–7 minutes per customer. System implementation demonstrated that SIBAKOS had a positive impact on Koko Salon by improving service quality and operational efficiency in the digital era.